Low density porous carrier based conceptual drug delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Pawar, Atmaram P. (Microporous and Mesoporous Materials, 2007)
Chronotherapy, a new approach for treating pathological conditions, is based on circadian rhythm. Present work conceptualizes a specific technology, based on combining floating and pulsatile principles to develop drug delivery system, intended for chronotherapy in arthritis. This approach was achieved by using low density microporous polypropylene, Accurel MP 1000 (R), as a multiparticulate carrier along with drug of choice ibuprofen. Carrier amount and solvent volume was kept invariant in designing this simple system by adsorbing drug via melting or solvent evaporation using different carrier: drug ratios. In solvent evaporation, methanol (M) and dichloromethane (DCM) were used. Drug loaded multiparticulate system was subjected to various characterization and evaluation parameters showing influence of adsorption process. Drug release study was performed in acidic environment using pH 1.2 HCl IP medium for 6 h to mimic gastric condition for evaluating gastroretention followed by basic environment using appropriate medium as phosphate buffer pH 7.2 IP for 3 h resembling transit. The release pattern showed influence of drug adsorption methods characterized by ever changing pore geometry with total release ranges in acidic medium as 10.7-27.6% and final release as 55.6-88.6%. Present drug delivery system devoid of any additives/excipients influencing drug release show distinct behaviour from other approaches/technologies in chronotherapy by (a) observing desired low drug release (11%) in acidic medium (b) overcoming the limitations of process variables caused by multiple formulation steps (c) reducing time consumption due to single step process (d) can be extended to controlled release also. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: chronotherapy; floating pulsatile drug delivery; low density porous carrier; melt adsorption; solvent polarity

Modulation and optimization of drug release from uncoated low density porous carrier based delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Poddar, Pankaj; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The purpose of this research work was to explore an application of uncoated porous drug carrier prepared by single-step drug adsorption for a delivery system based on integration of floating and pulsatile principles intended for chronotherapy. This objective was achieved by utilizing 3(2) factorial design, solvent volume (X (1)) and drug amount (X (2)) as selected variables, for drug adsorption using solvents, methanol, and dichloromethane (DCM), of varying polarity. Nitrogen adsorption (N(2)), scanning electron microscopy of cross-sections, and atomic force microscopy were done to study adsorption patterns and their effect on release pattern. Drug release study was customized by performing for 6 h in acidic environment to mimic gastroretention followed by basic environment akin to transit phase. Correlation between porous data from mercury and N(2) adsorption was probably studied for the first time. Observed regression analysis values for pore volume, surface area, and drug release indicated the influence of selected variables. Total release range in acidic medium was 12.77-24.57% for methanol, 8.79-15.26% for DCM, and final release of 69.45-92.23% for methanol, and 60.16-99.99% for DCM influenced by varying internal geometries was observed. Present form of drug delivery system devoid of any additives/excipients influencing drug release shows distinct behavior from other approaches/technologies in chronotherapy by (a) observing desired low drug release (8%) in acidic medium, (b) overcoming the limitations of process variables caused by multiple formulation steps and different characteristic polymers, (c) reducing time consumption due to single step process, and (d) extending as controlled/extended release.
Keywords: chronotherapy; floating pulsatile drug delivery system; low density porous carrier; pore data; solvent polarity

Novel/conceptual floating pulsatile system using high internal phase emulsion based porous material intended for chronotherapy - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Benson, James R.; Li, Nai-Hong; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The aim of the present study was to design a novel/conceptual delivery system using ibuprofen, anticipated for chronotherapy in arthritis with porous material to overcome the formulation limits (multiple steps, polymers, excipients) and to optimize drug loading for a desired release profile suitable for in vitro investigations. The objective of this delivery system lies in the availability of maximum drug amount for absorption in the wee hours as recommended. Drug loading using 3(2) factorial design on porous carrier, synthesized by high internal phase emulsion technique using styrene and divinylbenzene, was done via solvent evaporation using methanol and dichloromethane. The system was evaluated in vitro for drug loading, encapsulation efficiency, and surface characterization by scanning electron, atomic force microscopy, and customized drug release study. This study examined critical parameters such as solvent volume, drug amount, and solvent polarity on investigations related to drug adsorption and release mostly favoring low-polarity solvent dichloromethane. Overall release in all batches ranged 0.98-52% in acidic medium and 71-94% in basic medium. These results exhibit uniqueness in achieving the least drug release of 0.98%, an ideal one, without using any release modifiers, making it distinct from other approaches/technologies for time and controlled release and for chronotherapy.
Keywords: chronotherapy; floating pulsatile drug delivery system; high internal phase emulsion; ibuprofen; multiparticulate porous carriers